Role of Bangladesh Small and Cottage Industries Corporation in Poverty Reduction. (March 2015) - Haider, Mohammed Ziaul; Dutta, Champa Bati; Siddiqui, Ohidul Islam
This study investigates the role of Bangladesh Small and Cottage Industries Corporation (BSCIC) in poverty reduction of Bangladesh. A total of 91 workers are surveyed who work in BSCIC estates and non-BSCIC manufacturing firms in the south-west region of Bangladesh. This study has used both panel and cross-section approaches. The study findings indicate that BSCIC has a significant role in industrial expansion and poverty reduction in Bangladesh. The regression results reveal that BSCIC significantly influences household consumption and poverty reduction. A 1 per cent increase in income from BSCIC will increase the yearly household consumption by 0.73 per cent, whereas it is only 0.36 per cent in case of non-BSCIC income. The impact of income increase on consumption is more than double for the BSCIC group households in comparison with non-BSCIC group households. In cross-section analysis, the purchasing power parity (PPP) at local currency of US 1.25 is considered in this study to construct poverty line. The result shows that, for an increase in the income from BSCIC by US 1 per month, income over poverty line increases (or the poverty gap decreases) by US 0.028 per month per household on average. Therefore, this study suggests for planned expansion of BSCIC for poverty reduction in Bangladesh.